Unpacking reindeer husbandry governance in Sweden, Norway and Finland: A political discursive perspective - Löf, Annette; Raitio, Kaisa (2022)
In Sápmi and beyond, the practice of reindeer herding is under increasing pressure from competing for land use, large carnivores and climate change. The governing systems are, however, ill-equipped and unable to address resulting cumulative and interacting impacts. This has led to a difficult situation for reindeer herding due to the loss of land, functionality and flexibility, and proves a challenge for the Nordic states as the legitimacy of reindeer husbandry governance is increasingly contested. Addressing this challenge, this chapter unpacks the discursive and political dimensions of reindeer husbandry governance in Sweden, Norway and Finland. Guided by three broad questions: i) governing what, ii) governing how and iii) governing for and by whom, it explores how problem representations are constructed, handled and contested. The analysis shows that state-led governance was never in fact constructed to address herders’ concerns, but was, and remains, based on the states’ and competing land uses’ problem representations. The chapter, therefore, concludes by identifying the need to revisit the present understanding of “problems”, “solutions” and “visions” in reindeer husbandry governance. A key task will be to re-image, or actively seek to change the discursive construction of, reindeer herding as a system-to-be-governed and attune it to the perspectives of the herders.